Design Active Filter Based on Genetic Algorithm - Abdul-wbab, M.; AI-Azawi, R.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  lossy-FDNR  based  aclive  fil ter has an  important   property among  many  design  realizations. 'This includes  a significant reduction in component count particularly in the number  of OP-AMP which consumes   power.  However  theÂ·  problem  of  this   type  is the  large component spreads  which affect the fdter performance.In  this  paper   Genetic   Algorithm   is  applied   to  minimize   the component  spread   (capacitance  and  resistance  p,read). The minimization of these spreads allow the filter structure to be integrated since  the  minimum   omponent  spread  mean  minimum   chipÂ· area required  for fabrication.